Compatibility and combination of world W -boson mass measurements - Amoroso, S; Andari, N; Barter, W; Bendavid, J; Boonekamp, M; Farry, S; Grünewald, M; Hays, C; Hunter, R; Kretzschmar, J; Lupton, O; Pili, M; et al. (SpringerOpen, 2024)
The compatibility of W-boson mass measurements performed by the ATLAS, LHCb, CDF, and D0 experiments is studied using a coherent framework with theory uncertainty correlations. The measurements are combined using a number of recent sets of parton distribution functions (PDF), and are further combined with the average value of measurements from the Large Electron–Positron collider. The considered PDF sets generally have a low compatibility with a suite of global rapidity-sensitive Drell–Yan measurements. The most compatible set is CT18 due to its larger uncertainties. A combination of all mW measurements yields a value of mW=80, 394.6±11.5 MeV with the CT18 set, but has a probability of compatibility of 0.5% and is therefore disfavoured. Combinations are performed removing each measurement individually, and a 91% probability of compatibility is obtained when the CDF measurement is removed. The corresponding value of the W boson mass is 80, 369.2±13.3 MeV, which differs by 3.6σ from the CDF value determined using the same PDF set.